Prevalence of primary infertility and its associated risk factors in urban population of central India: A community-based cross-sectional study - Ashwini Katole; Ajeet V Saoji (Wolters Kluwer Medknow Publications, 2019)
Background: Primary infertility is a serious health issue that has profound socioeconomic and health implications on both the individual and society. Despite the important consequences of infertility, estimation of its prevalence is limited. Objective: The objective of the study is (1) to estimate the prevalence of primary infertility among women of reproductive age group in urban population of Central India and (2) to study its associated risk factors. Material and Methods: In a community-based cross-sectional study, all married women between 15 and 49 years of age in urban field practice area were included. The data were collected by face-to-face interview with the help of predesigned and pretested questionnaire. Results: The majority of the women (39.3%) belonged to 25-29 years of age group. The overall prevalence of primary infertility among reproductive age group women was 8.9% (51/570). Sociodemographic factors that had statistically significant association with infertility were age at marriage more than 25 years (P < 0.05), nuclear family (P < 0.05), higher education level (P = 0.04), employed women (P < 0.05), high socioeconomic status (P = 0.01), and family history of infertility (P < 0.05). Physiological factors that had statistically significant association with infertility were obesity (P = 0.03), age at menarche more than 14 years (P < 0.05) and irregular menstruation pattern (P < 0.05). Depression (P = 0.01) and stress (P < 0.05) were the psychological factors significantly associated with infertility. Conclusion: The prevalence rate of primary infertility in urban population of Central India was lower than reported trends of infertility from developing countries. Sound knowledge about various factors related to infertility can help health-care providers and policymakers to design and implement various policies.